Significant Effects of Oral Phenylbutyrate and Vitamin D3 Adjunctive Therapy in Pulmonary Tuberculosis: A Randomized Controlled Trial. - Akhirunnesa Mily; Rokeya Sultana Rekha; S M Mostafa Kamal; Abu Saleh Mohammad Arifuzzaman; Zeaur Rahim; Lamia Khan; Md Ahsanul Haq; Khaliqu Zaman; Peter Bergman; Susanna Brighenti; Gudmundur H Gudmundsson; Birgitta Agerberth; et al. (PLoS ONE)
Background Development of new tuberculosis (TB) drugs and alternative treatment strategies are urgently required to control the global spread of TB. Previous results have shown that vitamin D3 (vitD3) and 4-phenyl butyrate (PBA) are potent inducers of the host defense peptide LL-37 that possess anti-mycobacterial effects. Objective To examine if oral adjunctive therapy with 5,000IU vitD3 or 2x500 mg PBA or PBA+vitD3 to standard chemotherapy would lead to enhanced recovery in sputum smear-positive pulmonary TB patients. Methods Adult TB patients (n = 288) were enrolled in a randomized, double-blind, placebo-controlled trial conducted in Bangladesh. Primary endpoints included proportions of patients with a negative sputum culture at week 4 and reduction in clinical symptoms at week 8. Clinical assessments and sputum smear microscopy were performed weekly up to week 4, fortnightly up to week 12 and at week 24; TB culture was performed at week 0, 4 and 8; concentrations of LL-37 in cells, 25-hydroxyvitamin D3 (25(OH)D3) in plasma and ex vivo bactericidal function of monocyte-derived macrophages (MDM) were determined at week 0, 4, 8, 12 and additionally at week 24 for plasma 25(OH)D3. Results At week 4, 71% (46/65) of the patients in the PBA+vitD3-group (p = 0.001) and 61.3% (38/62) in the vitD3-group (p = 0.032) were culture negative compared to 42.2% (27/64) in the placebo-group. The odds of sputum culture being negative at week 4 was 3.42 times higher in the PBA+vitD3-group (p = 0.001) and 2.2 times higher in vitD3-group (p = 0.032) compared to placebo. The concentration of LL-37 in MDM was significantly higher in the PBA-group compared to placebo at week 12 (p = 0.034). Decline in intracellular Mtb growth in MDM was earlier in the PBA-group compared to placebo (log rank 11.38, p = 0.01). Conclusion Adjunct therapy with PBA+vitD3 or vitD3 or PBA to standard short-course therapy demonstrated beneficial effects towards clinical recovery and holds potential for host-directed-therapy in the treatment of TB. Trial registration clinicaltrials.gov NCT01580007.